The effect of market and learning orientations on organizational performance of manufacturing small and medium sized enterprises in Pakistan - Hussain, Jawad (2015)
Small and medium sized enterprises (SMEs) play an important role in strengthening the economy of developed and developing countries. The performance of SMEs depends on various factors. Among those factors include market orientation, learning orientation and entrepreneurial orientation practices. Previous literature has examined the effect of single orientation on organizational performance. Similarly, majority of the previous researches on orientations have been conducted in large organizations in developed countries while less attention has been given on SMEs in developing countries. The present study is an attempt to fill this gap by utilizing a multidimensional framework by empirically testing the effect of market orientation and learning orientation on organizational performance and the moderating effect of entrepreneurial orientation on the relationship between market orientation, learning orientations and SMEs performance within the cultural perspective of Pakistan. Data was collected from the top management of 213 SMEs located in the region of Sialkot, province of Punjab, Pakistan. Multiple regression analysis (MRA) was employed in order to study the nature and strength of relationship between market orientation and SMEs performance, as well as between learning orientation and SMEs performance. Hierarchical multiple regression analysis was utilized to test the moderating effects of entrepreneurial orientation on the relationship between market orientation, learning orientation and SMEs performance. Results indicated that both market orientation and learning orientation have a significant positive effect on SMEs performance. Findings revealed that entrepreneurial orientation does moderate the relationship between market orientation, learning orientation and SMEs performance. The results of the study provide guidelines and significant implications to help policy makers to enhance performance of SMEs by integrating multiple orientations in order to gain competitive advantage and superior performance. Furthermore, this study helps in enriching the current body of knowledge regarding the interrelationships between market orientation, learning orientation, entrepreneurial orientation and SMEs performance.